STRENGTHENING ZAKAT GOVERNANCE THROUGH ASSET-BASED COMMUNITY DEVELOPMENT: THE LEGALIZATION OF MOSQUE-BASED ZAKAT COLLECTION UNITS IN INDONESIA - Lianti, Riski; Utami, Cindy Ameilia; Widuri, Intan; Harpepen, Andi; Isnaini, Desi; Bahril, Muthi’ ‘Adilah; Afrianty, Nonie (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
Mosque-based zakat management plays a pivotal role in promoting community welfare, yet many Zakat Collection Units (UPZ) continue to operate without formal legalization. This situation undermines institutional accountability and constrains the optimization of zakat distribution. The aim of this article is to analyze the mentoring process for UPZ legalization at Babussalam Jami’ Mosque, Bengkulu, Indonesia, by applying the Asset- Based Community Development (ABCD) approach. The method combined observation, interviews, and community participation, structured through the stages of asset mapping, relationship building, community mobilization, visioning, and leveraging external resources. The findings reveal an enhanced collective awareness of the importance of legality, a communal agreement to initiate the decree for UPZ establishment, and the strengthening of zakat governance in a more participatory and transparent manner. These results demonstrate that the ABCD approach serves as an effective strategy for community empowerment in institutionalizing zakat management that is legal, accountable, and sustainable.